Mucoepidermoid carcinoma: A rare case report (Indian Journal of Case Reports, 2019)
Minor salivary gland carcinomas are rarely reported. Mucoepidermoid carcinoma (MEC) is one of the most common salivary gland malignancies. MEC accounts for 1% to 2% of major salivary gland neoplasms and 9% of minor gland tumors. It is most commonly seen in the parotid gland and usually appears as asymptomatic swelling. However, the palate is a frequent site when it occurs in the minor salivary glands. Follow-up of the patient is very important as local recurrence rate with conservative treatment is high. Here we are reporting a low-grade mucoepidermoid carcinoma involving palatal region in a 25-years-old female patient. The patient presented with a fast-growing swelling, invading the underlying anatomical structures and was treated successfully through the antrostomy procedure.